Upland rice response to soil acidity in Cerrado soil - Fageria, Nand Kumar (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this work was to evaluate the effects of soil pH on yield and its components and nutrients uptake by three upland rice cultivars/lines in a Dark-Red Latosol, clay loam texture of Cerrado region. A greenhouse experiment was conducted at the Embrapa-Centro Nacional de Pesquisa de Arroz e Feijão, Santo Antônio de Goiás, GO, Brazil. Soil pH levels created by application of lime were 4.6, 5.7, 6.2, 6.4, 6.6, and 6.8 and cultivars/lines tested were CNA 7460, Araguaia and CNA 7449. Dry matter and grain yield and yield components and nutrient absorption were significantly affected with soil pH. Adequate soil pH for yield and yield components was in the range of 5 to 5.4 and for the nutrients 4.6 to 5.5. These results suggest that rice cultivars tested were quite tolerant to soil acidity and it is possible to produce satisfactory crop in the pH range of 5 to 5.5.